Effect of agronomic practices in soil properties in hillsides. - Alfonso, Carlos A. (2006)
Trials were established in a highly eroded Ultisol soil of sandy loam texture, of poor fertility, acid, and low in phosphorus and organic matter, located in the locality of La Leña in Pinar del Río province, Republic of Cuba. A study was carried ont in 1996 in two watersheds, in which were implemented conservation practices consisting of live barriers of Gliricidia Sepium L. (in the first watershed) and Vetiveria Ziznoide L. (in the second watershed) complemented with ground cover of maize associated with legumes followed by beans in succession. Results showed slight changes in slope between barriers with respect to the initial value (10% vs 9%). Values of total dry biomass in the associations were 17 and 15 t/ha, and ground coverage at 30 days was more than 70%. Profuse root colonization presented by the associations indicated an improvement in porosity of the soil, reflecting a positive tendency in the internal structure that has evolved to a porous state. Yields of maize were 2900 and 2000 kg/ha, and of bean were 1800 and 1630 kg/ha, which are relatively high values, considering the degraded condition of the soil.